Low Overpotential Electrochemical Reduction of CO2 to Ethanol Enabled by Cu/CuxO Nanoparticles Embedded in Nitrogen-Doped Carbon Cuboids - Monther Q. Alkoshab; Eleni Thomou; Ismail Abdulazeez; Munzir H. Suliman; Konstantinos Spyrou; Wissam Iali; Khalid Alhooshani; Turki N. Baroud (Nanomaterials, 2023)
The electrochemical conversion of CO2 into value-added chemicals is a promising approach for addressing environmental and energy supply problems. In this study, electrochemical CO2 catalysis to ethanol is achieved using incorporated Cu/CuxO nanoparticles into nitrogenous porous carbon cuboids. Pyrolysis of the coordinated Cu cations with nitrogen heterocycles allowed Cu nanoparticles to detach from the coordination complex but remain dispersed throughout the porous carbon cuboids. The heterogeneous composite Cu/CuxO-PCC-0h electrocatalyst reduced CO2 to ethanol at low overpotential in 0.5 M KHCO3, exhibiting maximum ethanol faradaic efficiency of 50% at −0.5 V vs. reversible hydrogen electrode. Such electrochemical performance can be ascribed to the synergy between pyridinic nitrogen species, Cu/CuxO nanoparticles, and porous carbon morphology, together providing efficient CO2 diffusion, activation, and intermediates stabilization. This was supported by the notably high electrochemically active surface area, rich porosity, and efficient charge transfer properties.